THE SORGHUM MARKETING SYSTEM IN KAWALELO VILLAGE, DEMON PAGONG SUBDISTRICT, EAST FLORES REGENCY - Angelika Surat Larimanu; Marthen Robinson Pellokila; Siska Elvani (Buletin Ilmiah Impas, 2026)
The marketing system of sorghum commodities plays an important role in improving farmers’ welfare, especially in areas where sorghum is considered a leading commodity. This study aims to identify the various constraints faced by farmers in marketing their sorghum production and to analyze the marketing system using the Structure, Conduct, and Performance (SCP) approach in Kawalelo Village, Demon Pagong District, East Flores Regency. The method used in this study is a quantitative descriptive approach with a survey technique involving 58 respondents consisting of farmers and marketing institutions. Data were collected through interviews, field observations, and documentation. The results show that sorghum production has increased from year to year; however, this increase has not been accompanied by an optimal marketing system. The existing marketing channels involve several actors, namely farmers, collectors, and retailers. The marketing functions carried out include buying, selling, transportation, and storage activities. The main constraints faced by farmers include limited access to markets, high dependence on intermediaries, and the relatively simple marketing system applied. In addition, the high marketing margins and the low share of prices received by farmers (farmer’s share) result in relatively low farmer income. Therefore, the sorghum marketing system in the study area is considered inefficient and requires improvements, such as strengthening farmer institutions, expanding market access, and increasing efficiency in the marketing chain.